Desenvolvimento de um ChatBot para FAQutilizando ChatGPT - Moura, Ana Flávia Silva Aragão (2023)
A FAQ, regardless of the topic, can be very limited and may not meet the user's needs adequately, due to the funny and often complex questions and answers, making it difficult for some users to understand. With the advent of ChatGPT, we can obtain a chatbot with dynamic responses, however, it can return out-of-context and inappropriate responses. An alternative proposed to solve this problem is the development of a chatbot for FAQs using ChatGPT. Necessary work, therefore, we propose an interactive and adaptive chatbot, containing an inappropriate word suppressor and a context checker so that users' questions and answers are within the defined theme, and can also be personalized. Personalization relates questions to the topic covered and requests simplified explanations. The tool behaved promisingly, that is, in the test scenarios defined in actions such as assigning tasks during the test scenarios defined in these cases, questions to check the machine's vulnerabilities on inappropriate topics, for example, questions that trick the machine into giving an answer that it does not. corresponds to reality, disconnected questions and questions with variations with synonyms. In general, the solution is limited to responding within the defined theme, and not from a dictionary of valid contexts, resulting in concise and coherent responses, without losing personalization, according to the user's request.